Hierarchical nanoporous Pd1Ag1 alloy enables efficient electrocatalytic nitrogen reduction under ambient conditions. Issue 68 (6th August 2019) - Pang, Fangjie; Wang, Fei; Yang, Liting; Wang, Zhifeng; Zhang, Weiqing
Abstract : Hierarchical nanoporous Pd1 Ag1 nanoleaves act as highly-efficient and stable catalysts for electrochemical nitrogen reduction under ambient conditions. Abstract : Nanoporous Pd1 Ag1 nanoleaves with the merits of an appropriate atomic ratio, abundant low-coordinated surface atoms, efficient reactant accessibility and fast interfacial electron transfer kinetics exhibit superior catalytic activity towards the electrochemical nitrogen reduction reaction relative to nanoporous Pd1 Ag2 and Pd3 Ag1 alloys.